2023
DOI: 10.3390/mi14030644
|View full text |Cite
|
Sign up to set email alerts
|

Sub PPM Detection of NO2 Using Strontium Doped Bismuth Ferrite Nanostructures

Abstract: The present work investigates the NO2 sensing properties of acceptor-doped ferrite perovskite nanostructures. The Sr-doped BiFeO3 nanostructures were synthesized by a salt precursor-based modified pechini method and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The synthesized materials were drop coated to fabricate chemoresistive gas sensors, delivering a maximum sensitivity of 5.2 towards 2 ppm NO2 at 260 °C. The recorded values of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Additionally, while bulk BFO pellets have been used for sensing, there is a need for flexible conformable devices that enable good sensitivity and rapid response to gas, even in bent geometry. Sr-doped BFO has been reported for NO 2 sensing with an intricate fabrication procedure that involves processing in excess of 20 h as well as high-temperature sintering at 600 °C immediately before sensing measurements . This is not representative of an ambient environment that has humidity present, and the values obtained are synthetically enhanced due to this 600 °C thermal activation acting as an external driving force for sensing, while there is an additional constant operating temperature used for gas sensing from 260 to 500 °C.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, while bulk BFO pellets have been used for sensing, there is a need for flexible conformable devices that enable good sensitivity and rapid response to gas, even in bent geometry. Sr-doped BFO has been reported for NO 2 sensing with an intricate fabrication procedure that involves processing in excess of 20 h as well as high-temperature sintering at 600 °C immediately before sensing measurements . This is not representative of an ambient environment that has humidity present, and the values obtained are synthetically enhanced due to this 600 °C thermal activation acting as an external driving force for sensing, while there is an additional constant operating temperature used for gas sensing from 260 to 500 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Still, few reports are available that explore the gas-sensing properties of BFO, perhaps due to the relative difficulty of working with and understanding the electronic mechanism behind oxidizing gas sensing using a p-type semiconductor. The few reports that discussed BFO for gas sensing employed doped BFO as the active sensing layer but, more importantly, they all required operating temperatures in the range of 200 to 400 °C. , Specifically for NO 2 sensing, the W-doped BFO study displayed response/recovery times of 80/100 s, whereas the Pd-doped BFO study reported 90/110 s; they displayed the significant limitation of additional heating/operating temperatures up to 270 °C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations